2011
DOI: 10.1143/ptp.126.983
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Transition in Potts Models with "Invisible" States: Rigorous Proofs

Abstract: class of Potts models with "invisible" states was introduced, for which the authors argued, by numerical arguments and by a mean-field analysis, that a first-order transition occurs.Here we show that the existence of this first-order transition can be proven rigorously, by relatively minor adaptations of existing proofs for ordinary Potts models. In our argument, we present a random-cluster representation for the model, which might also be of interest for general parameter values of the model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…[9] for q > 1 and sufficiently large r. The transmutation of some second-order transitions into first-order transition by invisible states is therefore well established. In Ref.…”
Section: Introductionmentioning
confidence: 93%
“…[9] for q > 1 and sufficiently large r. The transmutation of some second-order transitions into first-order transition by invisible states is therefore well established. In Ref.…”
Section: Introductionmentioning
confidence: 93%
“…In this limit the system becomes one of non-interacting particles. Note that for the 2D Potts model with invisible states on a square lattice T c vanishes for large (q + r) as T c ≈ 2/ ln(q + r) [23].…”
Section: The Case Q =mentioning
confidence: 99%
“…Numerical simulations of the Potts model with invisible states in d = 2 dimensions gave solid evidence that the model exhibits a first-order phase transition at q = 2, 3, 4 for high values of r but it still remains a challenge for numerics to get a more precise estimate of r c [16]. Rigorous results prove the existence of a first-order regime for any q > 0, provided that r is large enough [23,24]. Exact results for the value of r c for the model are known for a Bethe lattice [25] too.…”
Section: Introductionmentioning
confidence: 95%
“…This model was originally suggested to explain why the phase transition with the q−fold symmetry breaking undergoes a different order than predicted theoretically [7,8,9]. Analysis of this model on different lattices has been a subject of intensive analytic [10,11,12,13,14,15,16] and numerical [7,8,9] studies. It has been shown that the number of invisible states (r) plays the role of a parameter, whose increase makes the phase transition sharper.…”
Section: Introductionmentioning
confidence: 99%